Hormonal modulation of novelty processing in women: Enhanced under working memory load with high dehydroepiandrosterone-sulfate-to-dehydroepiandrosterone ratios. (10th November 2016) - do Vale, Sónia; Selinger, Lenka; Martins, João Martin; Bicho, Manuel; do Carmo, Isabel; Escera, Carles
Highlights: High DHEAS/DHEA ratio was correlated to enhanced novelty-P3 amplitudes. This denotes enhanced acoustic novelty processing with high ratio. No deleterious effect on working memory processing was observed. A high ratio might enhance involuntary attention during working memory tasks. Abstract: Several studies have suggested that dehydroepiandrosterone (DHEA) and dehydroepiandrosterone-sulfate (DHEAS) may enhance working memory and attention, yet current evidence is still inconclusive. The balance between both forms of the hormone might be crucial regarding the effects that DHEA and DHEAS exert on the central nervous system. To test the hypothesis that higher DHEAS-to-DHEA ratios might enhance working memory and/or involuntary attention, we studied the DHEAS-to-DHEA ratio in relation to involuntary attention and working memory processing by recording the electroencephalogram of 22 young women while performing a working memory load task and a task without working memory load in an audio-visual oddball paradigm. DHEA and DHEAS were measured in saliva before each task. We found that a higher DHEAS-to-DHEA ratio was related to enhanced auditory novelty-P3 amplitudes during performance of the working memory task, indicating an increased processing of the distracter, while on the other hand there was no difference in the processing of the visual target. These results suggest that the balance between DHEAS and DHEA levels modulates involuntary attention during the performance of a task with cognitive load without interfering with the processing of the task-relevant visual stimulus.